2015
DOI: 10.1016/j.neuroscience.2015.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediator-induced modulation of GABAA currents in human sensory neurons

Abstract: The purpose of the present study was to characterize the properties of GABAA receptor currents in human sensory neurons. Neurons were obtained from adult organ donors. GABAA currents were recorded in isolated neurons. Both large inactivating low affinity currents and smaller persistent high affinity currents were present in all of the 129 neurons studied from 15 donors. The kinetics of human GABAA currents were slower than those in rat sensory neurons. GABA currents were completely blocked by bicuculline (10 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Human MRGPRX1 can be activated by both Mrgpra3 and Mrgprc11 agonists, although key differences in the pharmacological profiles of these receptors demonstrate distinct molecular mechanisms in mice versus humans 1317 . In support of these fundamental biological differences, GABA A receptor-mediated currents in cultured human sensory neurons were recently found to exhibit distinct biophysical features from those in rodents, demonstrating the importance of this type of preclinical approach 1821 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Human MRGPRX1 can be activated by both Mrgpra3 and Mrgprc11 agonists, although key differences in the pharmacological profiles of these receptors demonstrate distinct molecular mechanisms in mice versus humans 1317 . In support of these fundamental biological differences, GABA A receptor-mediated currents in cultured human sensory neurons were recently found to exhibit distinct biophysical features from those in rodents, demonstrating the importance of this type of preclinical approach 1821 .…”
Section: Introductionmentioning
confidence: 98%
“…Several recent studies have identified species differences and validated molecular mechanisms using human sensory neurons, but few have provided a detailed description of extraction or culturing methodologies 1821 . Here, we provide a detailed surgical extraction protocol for post-mortem access to human dorsal root ganglia (hDRG) immediately after organ procurement from consented donors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, using primary human neurons to validate preclinical rodent findings is an appealing strategy to improve the translational success of basic pain research findings. With this goal in mind, we and others have established approaches to obtain and use human sensory neurons to better understand human nociceptor physiology ( Baumann et al, 1996 ; Anand et al, 2006 ; Davidson et al, 2014 ; Han et al, 2015 ; Zhang et al, 2015 ; Sapio et al, 2016 ; Valtcheva et al, 2016 ; Rostock et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%